Benefits of using Sodium-Glucose Cotransporter 2 Inhibitors in patients after Acute Myocardial Infarction - Bezerra, Árnem Diogenes Bastos (2024)
Acute Myocardial Infarction (AMI) continues to be one of the main causes of morbidity and mortality worldwide. In this context, there has been growing interest in the role of Sodium-Glucose Cotransporter 2 Inhibitors (iSGLT2), with recent studies suggesting that these agents may have cardiovascular benefits and kidneys. Therefore, this work aims to analyze the benefits of using Sodium-Glucose Cotransporter 2 Inhibitors in patients after Acute Myocardial Infarction. This is an Integrative Literature Review, whose research was carried out in the Biblioteca Virtual em Saúde (BVS) and PubMed databases, using the following descriptors: “Sodium-Glucose Transporter 2 Inhibitors” and “ Myocardial Infarction”, together with the Boolean operator “AND”, observing articles published in the last 5 years, in English, Portuguese and Spanish. At the end of the research, 12 articles were selected. The results indicate that the use of iSGLT2 in patients after AMI is associated, in the long term, with improvements in cardiac remodeling, lower chances of developing HF and hospitalizations for decompensated HF, reduced chances of new cardiovascular events, and improved renal function with lower chances of developing Acute Kidney Injury. These benefits were observed even in patients who underwent surgical interventions to treat AMI, regardless of gender, age and presence or absence of DM. In patients who use iSGLT2 acutely, shortly after the cardiac event, they also showed benefits, with a reduction in the levels of structural and functional cardiac markers, such as NT-proBNP, indicating a potential reduction in the severity and extent of ischemic injury.